Latitudinal extent of the equatorial electrojet effects in the Indian zone - Rastogi, R.G. (My University, 1991)
Using the H and Z components of the geomagnetic field at eight observatories in India, situated within a narrow longitudinal zone and spread from 0 deg to 25 deg dip latitudes, it has been shown that the effects at the ground during strong counter electrojet events can be seen over the entire latitudinal extent of the Indian zone, not only over the narrow zone near the dip equator. Some disturbances are shown to occur at low latitudes, causing simultaneous decrease of the equatorial electrojet current and increase of the Sq current. These abnormal changes in the low-latitudes geomagnetic field are suggested to be due to local modifications of the lunar and solar tides rather than due to the imposition of additional electric fields at only the equatorial stations.
Keywords: Equatorial electrojet; Atmospheric electricity; Geomagnetism; Diurnal variations; India